Effects of armadin on hepatic transaminases in rats with acute generalized peritonitis on the background of diabetes mellitus - Regeda, M.; Verveha, B.; Melnyk, N. (Journal of Education, Health and Sport, 2021)
The article discusses the issues about the effect of the Armadin on the hepatic transaminase in rats with acute generalized peritonitis on the background of diabetes mellitus. The experiment was performed on 48 white male adult rats, which were divided into two groups. The experimental group – animals with simulated acute generalized peritonitis against the background of streptozotocin-induced diabetes with the drug “Armadin” (ethylmethylhydroxypyridine succinate) application (n=24). The control group – animals with simulated acute generalized peritonitis against the background of streptozotocin-induced diabetes without pharmacocorrection (n = 24). Diabetes mellitus was simulated by a single intraperitoneal injection of streptozotocin at the dose of 60 mg/kg. Acute generalized peritonitis was induced with 10% faecal suspension in a dose of 0.5 ml per 100 g of animal weight in the abdominal cavity of laboratory animals by puncture method. Every day for 6 days, rats of experimental group received the drug “Armadin” at the doses of 100 mg/kg. We found a probable decrease in aminotransferase activity on day 3 of the study in rats of the experimental group after administration of Armadin. Thus, ALT activity decreased by 26.7%, and AST activity – by 25.9% compared to the control group. On the 7th day of the study, the activity of ALT in the blood of rats of the experimental group decreased to 0.50 ± 0.03 mmol/l, which was 49.5% lower than the control group of rats in this period of the experiment. Similar changes are observed in the study of AST activity, where, accordingly, it decreased by 48 % relative to control. The positive effect of the drug "Armadin" on the body of rats, with AGP on the background of STZ-induced diabetes, is manifested by the restoration of the functional state of the liver.